Wayward Pines : Wayward - Book 2 - Crouch, Blake; Garcia, Paul Michael (Grand Haven, Michigan : Brilliance Audio, 2013)
Wayward Pines may look like the perfect small town, but it is far from it. The first clue is the electric fence topped with sharp wire. Then there are the residents. They dont know how they arrived but they are told how to live their lives while being under constant surveillance. Deep down everyone wants to leave, but those who leave pay a hefty price. Wayward Pines sheriff Ethan Burke is one of few who knows the truth about the town. And he knows what is lurking on the other side of the fence.
Keywords: United States. -- Federal Bureau of Investigation; Employees; Fiction; Sheriffs -- Fiction; Small cities; Fiction; Electric fences; Fiction; Electronic surveillance; Fiction; Idaho -- Fiction; Detective and mystery fiction; Thrillers (Fiction); Audiobooks; Sound recordings